2012
DOI: 10.1007/jhep05(2012)080
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Rényi entropies in conformal field theories and holography

Abstract: An entanglement Rényi entropy for a spatial partition of a system is studied in conformal theories which admit a dual description in terms of an anti-de Sitter gravity. The divergent part of the Rényi entropy is computed in 4D conformal N = 4 super Yang-Mills theory at a weak coupling. This result is used to suggest a holographic formula which reproduces the Rényi entropy at least in the leading approximation. The holographic Rényi entropy is an invariant functional set on a codimension 2 minimal hypersurface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 51 publications
8
75
0
Order By: Relevance
“…This result can be independently confirmed using the vector heat kernel on manifolds with a conical singularity [22], [23]. However, to our knowledge, a field theory calculation via the approach developed in [13] reproducing this result is absent (besides directly adopting the anomaly coefficients).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…This result can be independently confirmed using the vector heat kernel on manifolds with a conical singularity [22], [23]. However, to our knowledge, a field theory calculation via the approach developed in [13] reproducing this result is absent (besides directly adopting the anomaly coefficients).…”
Section: Introductionmentioning
confidence: 51%
“…The main reason we consider a different approach in this paper to study the entanglement entropy of gauge fields instead of adopting the traditional replica method is that one is already able to obtain the expected central charge-entropy relation (8) using the conical method [22]. On the other hand, it is well-known that the conical singularity causes subtle issues such as generating a contact term [32].…”
Section: Conical Contact Entropymentioning
confidence: 99%
“…We have extracted the logarithimic term from the Wald entropy as it requires only information about the bulk space time around the boundary. Although we have demonstrated that the regularized squashed cones of [26] can be used to compute EE, a naive application of this procedure would not work for Renyi entropies [10,52,53] for general n although the starting metric is regular. Except near n = 1, where we saw that the universality in Renyi entropy [10,47,49,50] pertaining to ∂ n S n | n=1 bears out, the result for a general n would be regularization dependent -for instance we will need to know details about f (r, b) away from r = 0.…”
Section: Jhep01(2014)021mentioning
confidence: 99%
“…For the theory consisting of n s free real scalars, n f free Weyl fermions and n v free vectors, the functions f a (n) and f c (n) have been calculated explicitly in [8,15,[36][37][38][39]. We list the results as follows:…”
Section: The Story Of Free Cftsmentioning
confidence: 99%